2020
DOI: 10.3390/w12082240
|View full text |Cite
|
Sign up to set email alerts
|

WWTP Effluent Quality Improvement for Agricultural Reuse Using an Autonomous Prototype

Abstract: Wastewater reuse presents a promising way to mitigate the risk to global water resources and achieve sustainability in water, especially in agricultural areas in the southeast of Spain, such as the Murcia region. However, the risks related to the presence of contaminants of emerging concern (CECs) or pathogenic microorganisms in wastewater treatment plant (WWTP) effluent suggest the need to implement effective and relatively low-cost tertiary treatments. With this aim, a self-sustainable pilot prototype based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…For this research, adsorption by granular activated carbon showed low removal rates of antibiotics, antiepileptics, and most analgesics [ 31 ]. On the other hand, Sun et al (2017), in a study with a pure experimental design, employed adsorption by powdered activated carbon for the removal of hormones, achieving removal rates of 34.4%, 83.3%, and 99.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this research, adsorption by granular activated carbon showed low removal rates of antibiotics, antiepileptics, and most analgesics [ 31 ]. On the other hand, Sun et al (2017), in a study with a pure experimental design, employed adsorption by powdered activated carbon for the removal of hormones, achieving removal rates of 34.4%, 83.3%, and 99.…”
Section: Resultsmentioning
confidence: 99%
“… Removal of pharmaceuticals from municipal wastewater in studies with a quasi-experimental design (M01 = [ 27 ], M03 = [ 29 ], M05 = [ 31 ], M17 = [ 49 ], M09 = [ 35 ], M04 = [ 30 ], M10 = [ 36 ]). …”
Section: Figurementioning
confidence: 99%
“…When the World Water Assessment Program (WWAP) stated treated wastewater as a reliable and sustainable water resource, the national and international landscape started to change, and since then, the development of regulations on this issue has been ever more frequent in national and international institutions to ensure high standards of water quality [63]. The European Union developed specific regulation (EU 2020/741) where minimum requirements for using reused water in agriculture guarantee a high level of quality in order to protect the environment and human health and foster a circular economy [64]. For its part, the World Health Organisation (WHO) has also evolved regulations regarding the reuse of wastewater to properly ensure human safety [62].…”
Section: Introductionmentioning
confidence: 99%
“…Wastewater reuse presents a promising route to the achievement of water sustainability. It can be applied for diverse uses to share the burden on freshwater sources, where the use of reclaimed water has proven to be an excellent approach to dealing with water scarcity [4,5]. In Taiwan, the uneven spatial and temporal distribution of water resources, difficulties regarding water storage due to the terrain, high levels of urbanization, and rapid industrialization have led to low water-use efficiency as well as to water shortages.…”
Section: Introductionmentioning
confidence: 99%